2022
DOI: 10.1155/2022/1381542
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Body Mass Index and Body Composition in Patients with Schizophrenia: A Case-Control Study

Abstract: Background. Antipsychotics exert metabolic side effects, and prolonged treatment with antipsychotics causes changes in body weight and muscle composition. Nevertheless, reports on the changes in body composition of patients with schizophrenia have been limited. This study is aimed at comparing the body mass index and body composition of patients with schizophrenia with healthy individuals in Indonesia. Methods. A total of 195 patients with schizophrenia (148 males and 47 females) and 195 healthy individuals ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Results for underweight participants with schizophrenia varied in previous research [ 7 , 9 , 25 , 26 , 27 ]. With only 2% of the total sample categorized as underweight, the results of Costa et al [ 12 ] are closer to the presented ones.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Results for underweight participants with schizophrenia varied in previous research [ 7 , 9 , 25 , 26 , 27 ]. With only 2% of the total sample categorized as underweight, the results of Costa et al [ 12 ] are closer to the presented ones.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, caregivers smoked in similar shares as beneficiaries. Results reported by Marthoenis et al [ 9 ] showed that 36.2% of patients and 63.8% of the control group were married. Marriage rates among beneficiaries (4.4 %) were substantially lower than reported in previous research, unlike rates among caregivers (68.4%).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations